Performance analysis of a refrigerant extracting twin screw compressor employed in multi-temperature heat pump systems. (July 2016) - Zhao, Zhaorui; Tian, Yafen; Hou, Feng; Xing, Ziwen
Highlights: A refrigerant extracting twin screw compressor designed for multi-temperature heat pumps is introduced. The working process of the compressor and performance of the system are studied numerically. The influence of various features on compressor's working process is analyzed. Modified heat pump systems have significantly higher COP compared with the traditional system. Abstract: Heat pump systems are widely used in heat recovery applications where high temperature waste heat is abundantly available. High temperature heat pumps are capable of recovering heat from the condenser of a refrigeration system to supply heat for processing or heating. However, conventional systems are unable to supply heat at more than one temperature level, while significant efficiency loss is caused by the large condensing temperature difference between high and mid temperature condensers. In this paper, a novel type of refrigerant extracting screw compressor and a modified system is designed. Mathematical models are formulated for the working process and performance prediction. Therefore, the pressure of refrigerant within the compressing chamber and the COP of the heat recovery multi-temperature heat pump system are calculated. Furthermore, the influence of the internal volumetric ratio, operating condition, properties of refrigerant extraction and mid-stage condensing temperature on the performance are discussed.